2016 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/p.27224
|View full text |Cite
|
Sign up to set email alerts
|

Work in Progress: Evaluation of Biomechanics Activities at a College-Wide Engineering Outreach Event

Abstract: Jarred Kaiser is a post-doctoral researcher at Boston University. He has previously earned degrees in Mechanical Engineering from the Ohio State University (B.S.) and University of Wisconsin -Madison (M.S., Ph.D.). His research focuses on imaging the multiscalar effects of altered mechanics due to injury/surgery on tissue health. Joseph Towles PhD, University of Wisconsin -MadisonJoseph Towles is a Faculty Associate in the Department of Biomedical Engineering at the University of Wisconsin-Madison. Joe complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
(3 reference statements)
2
2
0
Order By: Relevance
“…As a result, the workshop presented in this article was born. Similar activities with interesting results can be found in [5,6], where the realization of parallel events or activities to teach engineering principles demonstrate the potential for hands-on, biomechanicsbased activities to engage students. Also, Ref.…”
Section: Introductionsupporting
confidence: 54%
“…As a result, the workshop presented in this article was born. Similar activities with interesting results can be found in [5,6], where the realization of parallel events or activities to teach engineering principles demonstrate the potential for hands-on, biomechanicsbased activities to engage students. Also, Ref.…”
Section: Introductionsupporting
confidence: 54%
“…In this study, we explored the impact of biomechanics-based activities on situational and individual interest among K-12 students while considering gender, grade-level and ethnicity. Our results suggest that biomechanics-based activities can engage students at high and low levels of interest in biomechanics, similar to the finding from a previous study in our group (Francis et al, 2016), and can positively impact their consideration of careers in engineering. We were unable to engage low individual-interest girls more than boys, and ethnicity and grade-level were not influential factors.…”
Section: Discussionsupporting
confidence: 88%
“…Biomechanics is a highly relatable, interdisciplinary field with ties to engineering, medicine, and athletics. In a previous study (Francis et al, 2016), we found biomechanics-based activities had potential for teaching biomechanics to 5 th -8 th grade students with presumably varying interest levels and demographic backgrounds. Our current study investigated the impact of similar biomechanics-based activities on situational and individual interest among K-12 students while considering gender, grade-level, and ethnicity.…”
Section: Impact Of Biomechanics-based Activities On Situational and Imentioning
confidence: 84%
“…Biomechanics is a highly relatable, interdisciplinary field with ties to engineering, medicine, and athletics. Previous studies at a college-wide engineering outreach event (Francis et al, 2016;Francis et al, 2017) have demonstrated the potential for hands-on, biomechanics-based activities to teach engineering principles to K-12 students. A recent study (Francis et al, 2017) indicated that boys participating in these activities had a higher interest in engineering than girls.…”
Section: Introductionmentioning
confidence: 99%